ENGLISH FOR MARINERS COURSEBOOK: HOW DOES READABILITY FORMULA RATE THE READABILITY LEVEL OF TEXTS? - Giovanni Oktavinanda; Syafni Yelfi Siska; Kartika Harda Putri; Endah Anisa Rahma; Al Zuhri Al Zuhri (Universitas PGRI Palembang, 2022)
Readability level of marine texts do influences cadets’ ability in comprehending Maritime English reading materials. This research investigates the readability level of texts in English for Mariners, an English Maritime coursebook published by Language Competence Certification Tools for the Vocations (LCCTV) used for first-year cadets at West Sumatera Merchant Marine Polytechnic. To this end, 10 selected texts from 10 units were analysed. The Flesch-Kincaid Reading Ease was utilized as readability formula to assess the readability level of texts. The findings revealed that 10% text was categorized as extremely difficult, 30% texts were difficult, 30% texts were fairly difficult, 10% text was average, 10% text was fairly easy, and 10% text was easy to read. Thus, English for mariners coursebook is readable for cadets even though few texts are too easy to comprehend.